DNA Barcoding Using the Chloroplast Gene MatK for Genetic Diversity Analysis of Lansium domesticum Corr. Plants Growing in South Sumatra, Indonesia - Wardana, Singgih Tri; Hanum, Laila; Nursela, Dewi; Aminasih, Nita; Kasiamdari, Rina Sri (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
Lansium domesticum Corr. known as duku, langsat, and kokosan is a popular fruit in Indonesia, particularly in South Sumatra. Furthermore, the fruit is cherished in this region because of the nice smell, sweet taste, and high economic value. Until now, South Sumatra local duku is rarely investigated, even though information on the genetic diversity of the germplasm is useful in supporting breeding and conservation programs. Therefore, this study aimed to determine the genetic diversity and phylogenetics of local duku and langsat (Lansium domesticum) based on matK gene DNA barcoding. DNA genome was extracted using Tiangen Plant Genomic DNA Kit DP305, then amplified using GoTaq Green Master Mix (Promega) and primers 3F_KIM-F and 1R_KIM-R. The product was sequenced by 1st Base Singapore and seven amplification results had a DNA size of 900 bp. The results showed that the matK gene is capable of determining Lansium domesticum interspecies. According to the DNA sequence phylogenetic analysis conducted using the maximum likelihood method, all the DNA samples were designated as Lansium domesticum Corr. with a fairly high genetic variation, indicated by DNA sequence differences caused by gene mutations. DNA Barcoding Menggunakan Gen Kloroplas MatK untuk Analisis Keragaman Genetik Tanaman Lansium domesticum Corr. yang Tumbuh di Sumatera Selatan, Indonesia ABSTRAK: Lansium domesticum Corr. yang dikenal dengan sebutan duku, langsat, dan kokosan merupakan buah yang populer di Indonesia, khususnya di Sumatera Selatan. Selain itu, buah ini digemari di daerah ini karena baunya yang harum, rasanya yang manis, dan bernilai ekonomis tinggi. Hingga saat ini, duku lokal Sumatera Selatan jarang diteliti, padahal informasi mengenai keragaman genetik plasma nutfahnya bermanfaat dalam mendukung program pemuliaan dan konservasi. Oleh karena itu, penelitian ini bertujuan untuk mengetahui keragaman genetic dan filogenetik duku dan langsat (Lansium domesticum) berdasarkan DNA barcoding gen matK. DNA genom diekstraksi menggunakan Tiangen Plant Genomic DNA Kit DP305, kemudian diamplifikasi menggunakan GoTaq Green Master Mix (Promega) dan primer 3F_KIM-F dan 1R_KIM-R. Produk tersebut disekuensing oleh 1st Base Singapore dan tujuh hasil amplifikasi memiliki ukuran DNA 900 bp. Hasil penelitian menunjukkan bahwa gen matK mampu mengidentifikasi Lansium domesticum antarspesies. Berdasarkan analisis filogenetik sekuens DNA yang dilakukan dengan metode kemungkinan maksimum, semua sampel DNA ditetapkan sebagai Lansium domesticum Corr. dengan variasi genetik yang cukup tinggi, ditunjukkan oleh perbedaan sekuens DNA yang disebabkan oleh mutasi gen.